An Analysis of Students Pronunciation Errors - Maiza, Masfa (English Language Education Study Program, 2020)
This study deals with students pronunciation errors in English consonants. It was conducted under the consideration that pronouncing English words played an important role. A descriptive qualitative was used as the research method. The subject of this research was forty seven students of first year of English Language Education Study Program at Pamane Talino College of Education, Landak Regency, West Kalimantan. Pronunciation test and interview were used to collect data. The result reveals that the students got difficulties in pronouncing /θ/, /ð/, /ʃ/, /ʒ/, /tʃ/ and /dʒ/. Then, the factors affecting the students’ pronunciation are interference, phonological system and motivation.